Władysław Gomułka a sprawa Katynia - Wasilewski, Witold (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article discusses the position of Władysław Gomułka, the leading Polish communist official, the leader of the Polish Workers’ Party (PPR) and later of the Polish United Workers’ Party (PZPR), on the Katyń crime committed by the Soviets on Polish prisoners of war – officers of the Polish Army. Throughout his political career, Gomułka consistently and by various means acted to hide the truth on the Soviet responsibility for Katyń crime. When in April 1943 Germans announced to the world that in 1940 the officers of the Polish Army were murdered by the Soviets in the Katyń forest, Gomułka gave his support to the untruthful version of events presented by the Soviet authorities. Soviet communists, followed also by Polish communists, falsely blamed the German Third Reich for the Katyń massacre and accused German authorities of staging in 1943 an anti-Soviet provocation, allegedly supported by the Polish Government in exile in London and the Underground Movement in Poland. From 1943 till 1948 Gomułka, as an activist of PPR, promoted Katyń lie, in particular highlighting the thesis on participation of Polish right-wing circles in the provocation against the Soviet Union. During the German occupation he did it mainly in communist underground press, and from mid-1944 he also used his public speeches to propagate the lies. From 1956 till 1970, as the leader of PZPR, Gomułka still supported the Katyń lie by using censorship to suppress any discussion on it, while not abandoning the false Soviet version of the events blaming Germans for the massacre. Only when he lost power and finished his political career in 1970, Gomułka conceded in his diaries that the Soviet story about Katyń was false, but he still insisted that he did the right thing when he supported the lies about Katyń.